1995
DOI: 10.1002/pola.1995.080330111
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic synthesis of polymers. III. Formation of a high molecular weight polyester through limitation of hydrolysis by enzyme‐bound water and through equilibrium control

Abstract: Enzyme‐catalyzed preparation of polymers offers several potentially valuable advantages over the usual polymerization procedures and has been studied for several years. A significant limitation on the polyesters prepared to date has been the low molecular weights achieved. The present studies have established that, in the polycondensation of bis(2,2,2‐trifluoroethyl) glutarate with 1,4‐butanediol using porcine pancreatic lipase as the catalyst, this limitation arises from at least two sources: hydrolysis of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…The lipase, therefore, may recognize the polymer as an acyl acceptor, particularly the ends of the chains, and catalyze ester cleavage leading to lower molecular weight polymers. The depolymerization phenomena of enzyme-catalyzed polyesters have been previously reported (Binns et al, 1998;Brazwell et al, 1995;Chaudhary et al, 1997aChaudhary et al, , 1997bLinko et al, 1995;Uyama et al, 1999). Specifically, Chaudhary and coworkers extensively investigated the role of water in biocatalytic AA-BB polycondensed materials (DVA/1,4-butanediol).…”
Section: Synthesis Of Selected Polyestersmentioning
confidence: 96%
See 1 more Smart Citation
“…The lipase, therefore, may recognize the polymer as an acyl acceptor, particularly the ends of the chains, and catalyze ester cleavage leading to lower molecular weight polymers. The depolymerization phenomena of enzyme-catalyzed polyesters have been previously reported (Binns et al, 1998;Brazwell et al, 1995;Chaudhary et al, 1997aChaudhary et al, , 1997bLinko et al, 1995;Uyama et al, 1999). Specifically, Chaudhary and coworkers extensively investigated the role of water in biocatalytic AA-BB polycondensed materials (DVA/1,4-butanediol).…”
Section: Synthesis Of Selected Polyestersmentioning
confidence: 96%
“…Brazwell et al (1995) reported the biocatalytic synthesis of poly(1,4-butanediol glutarate) from bis(2,2,2-trifluoroethyl) glutarate (B) with 1,4-butanediol (2) whereby periodic vacuum was applied to improve the M w from 2,600 to 10,600 Da in reactions conducted for 96 h. GPC analysis of the polymer formed in the B2 well of our array indicated an M w of 4,150 Da and a polydispersity of 1.9. The polymers formed in the well-scale showed lower M w than the latter and may be due to the lack of vacuum applied to the reaction.…”
Section: Enzyme-catalyzed Array-based Polycondensationsmentioning
confidence: 97%
“…The calibration curves for SEC analysis were obtained by using polystyrene standards, because the molecular weight of the polymer from 1a and 2b that had been determined by light scattering agreed with that determined by SEC analysis using polystyrene standards. 9 The highest molecular weight (2.1 ϫ 10 4 ) was achieved by using lipase PC catalyst (entry 4). When using 1b, a similar tendency was observed; the same four lipases were active for the polymerization and the polymer yields were not very different from each other (ca.…”
Section: Enzyme Screen For Polymerization Of Dicarboxylic Acid-divinymentioning
confidence: 99%
“…High (>10 000) molecular weight polyesters are an important class of polymers whereas low (<2000) molecular weight polyols are used as starting intermediates in synthesis of polyurethane elastomers (Sanders and Frisch, 1992). The molecular weight achievable during enzymatic synthesis is determined by two factors (Morrow, 1992; Brazwell et al, 1995; Chaudhary et al, 1996c)‐the equilibrium in the reaction mixture and the role of undesirable side reactions leading to destruction of active functional groups (Chaudhary et al, 1996c). These factors have combined to significantly limit the achievable molecular weight in biocatalytic systems at reasonable enzyme concentrations (Table 1).…”
Section: Introductionmentioning
confidence: 99%